(untitled) (Training and Practice : Journal of Educational Sciences, 2013)
This study aims at exploring Preservice English teachers’ use of coping strategies for speaking and listening problems. The Oral Communication Strategy Inventory (OCSI) developed by Nakatani (2006) was used to collect data for the study. The participants were preservice English teachers at a Turkish University. The findings emanating from the questionnaire indicate that there is a significant difference in coping strategies for speaking problems in subscales such as Fluency-Oriented Strategies (FOS), Message Abandonment Strategies (MAS), and Social Affective Strategies (SAS) in favor of those students who had either spent at least one semester at a European university as a part of the Erasmus Student Exchange Program or those who reported that they frequently interacted with native speakers. A significant difference was also observed in the Fluency-Maintaining Strategies (FMS) subscale of the questionnaire relating to coping strategies for listening problems which was in favor of the same group of preservice English teachers. From the general evaluation of all the subscales of coping strategies for both speaking and listening problems, preservice English teachers revealed the lowest mean scores in the MAS subscale in speaking and in the Less Active Listening Strategies (LALS) subscale in listening problems, while they were highest in Negotiation for Meaning While Speaking (NMWS), Nonverbal Strategies While Speaking (NSWS) and Negotiation for Meaning While Listening (NMWL) subscales. These results suggest that the use of the target language in real communication settings contributes more meaningfully to the development of oral communication skills.